PEMECAHAN MASALAH MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PISA KONTEN SPACE AND SHAPE DITINJAU DARI GENDER - Luthfiah Aisyah Romadhoni; Rini Setyaningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
There are many studies that examine students' abilities, but there are still few that examine students' ability to solve PISA problems with konten space and shape. This research uses Polya indicators, namely understanding problems, planning for problem solving, implementation of planning, and re-checking. Describing students' ability to solve problems with PISA questions reviewed from gender differences is the goal of this study. The method used is qualitative with a data triangulation technique that takes data by the test method and interviews involving 6 subjects consisting of 3 male subjects and 3 female subjects. The result of this study is that female students are superior to male students in problem-solving ability. Lack of scrupulousness makes male students in problem-solving ability under female students. Mistakes in male students that often occur are at the stage of carrying out problem-solving planning and re-checking the results of the answers obtained, while female students only occur during the re-checking process.